Kekasaran permukaan pada pemesinan frais mikro Ti 6Al- 4V ELI (extra low intertitial) - Gusri Akhyar Ibrahim; Endra Saputra; Suryadiwansa Harun; Eko Agus Supriyanto; Armulani Patihawa (Universitas Muhammadiyah Metro, 2019)
One of the ingredients that are popular now is titanium, but titanium is a material that is difficult to process using conventional milling machining because of the poor thermal conductivity of the material so that the high-temperature machining process produced in the cutting zone causes plastic deformation in cutting tools and increased chemical reactivity in titanium. High-speed micro-milling machining can be used for micro machining of hard metals or alloys that are difficult to achieve at low speeds. Micro milling machining in titanium material 6Al-4V ELI with variations in milling tool diameter 1 and 2 mm, spindle speed 10.000 and 15.000 rpm, feed 0,001 and 0,005 mm/rev, depth of cut 100 and 150 μm, which then do data processing using the method taguchi full factorial and theoretical analysis. The results showed that the diameter of the tool and into the depth of cut the most effect on surface roughness, the greater the tool diameter of the milling produced a smaller roughness value, this is inversely proportional to the depth of the cut. The lowest roughness value is 0,26 and the highest roughness value is 0,9. Keywords: Micro milling machining, titanium 6Al-4V ELI, surface roughness.